Assessment of Safety Profile of Activated Curcumin C3 Complex (AC3®), Enriched Extract of Bisdemethoxycurcumin from the Rhizomes of Curcuma longa - Muhammed Majeed; Sarang Bani; Anjali Pandey; Muhamad Ibrahim A.; Smitha Thazhathidath (Journal of Toxicology, 2023)
The present work was carried out to investigate the toxic effects of Activated Curcumin C3 Complex (AC3®) through the methods of acute, subacute, subchronic, reproductive/developmental toxicity, and genotoxicity when administered orally in experimental rodents. The studies were carried out in line with OECD principles of good laboratory practice. A single-dose acute oral toxicity study was conducted on female Wistar rats that produced no toxic effects after 14 days (the observation period) of treatment. Subacute, subchronic, and reproductive/developmental studies were conducted in Wistar rats, divided equally into vehicle control, 125, 250, and 500 mg/kg dose groups along with recovery groups for vehicle control and high dose. In all the studies, there were no abnormal clinical signs/behavioral changes, reproductive and developmental parameters, or gross and histopathological changes. Likewise, no alteration was found in the body weight, hematology, and other biochemical parameters. Also, it did not show mutagenicity in the in vitro AMES test or clastogenicity and aneugenicity in the in vivo micronucleus test, indicating that AC3® did not induce any genotoxic effects. This revealed that oral administration of AC3® is safe in rodents, nonmutagenic, and had no observed adverse effects under experimental conditions.